Production and characterization of active recombinant human factor II with consistent sialylation. Issue 9 (12th May 2017) - Lee, Jeong H.; Reier, Jason; Heffner, Kelley M.; Barton, Christopher; Spencer, David; Schmelzer, Albert E.; Venkat, Raghavan
ABSTRACT: Coagulation factor II (prothrombin; FII) is the pre‐proteolyzed precursor to thrombin in the coagulation cascade. It has 10 sites of gamma‐carboxylation, which are required for its bioactivity, and is N‐ glycosylated at three of four putative sites. Production of recombinant human FII (rhFII) using a platform fed‐batch process designed for monoclonal antibody production resulted in low levels of gamma‐carboxylation and sialylation. There have not been any prior reports of successful process development and clinical manufacture of rhFII with optimal, consistent gamma‐carboxylation and sialylation. In order to develop such a fed‐batch process, various process parameters were evaluated to determine their impact on product quality. Process temperature and temperature shift timing were important for both sialic acid level and gamma‐carboxyglutamate (Gla) level. In addition, vitamin K concentration and the type of surfactant used for preparation of vitamin K stock solution were also important for gamma carboxylation. A fed‐batch study performed with various medium additives known to be involved in the N‐ glycosylation pathway, such as N‐ acetyl‐d ‐mannosamine (ManNAc), galactose (Gal), dexamethasone, and manganese sulfate, increased the level of sialylation and enabled the elucidation of some potential bottlenecks in the sialylation pathway. The optimized process based on these studies yielded a reduction in the level of missing Gla by 0.4 moles per mole of rhFII in cell culture and a nearly threefold increase in sialic acid level. The process was successfully implemented at the 2000 L scale where a high Gla level and sialylation levels were achieved in all GMP lots. Biotechnol. Bioeng. 2017;114: 1991–2000. © 2017 Wiley Periodicals, Inc. Abstract : Maximizing the level of gamma carboxylation and controlling sialylation are critical for the manufacture of biologically active recombinant human factor II with consistent sialylation. The authors demonstrate cell culture process development approaches and utilization of in‐process sample analytical techniques to achieve these goals. Successful optimization for both gamma carboxylation and sialylation is discussed along with demonstration of process scalability in GMP manufacturing.